Chicken soup for the soul grandmothers : 101 stories of love, laughs, and lessons from grandmothers and grandchildren - Canfield, Jack 1944-; Hansen, Mark Victor; Newmark, Amy (Chicken Soup for the Soul Publishing, 2011)
A collection of 101 true stories by grandmothers and grandchildren about their mutual love for each other and the experience of becoming and being a grandmother.